A Photo Touch on Amines: New Synthetic Adventures of Nitrogen Radical Cations - Maity, Soumitra; Zheng, Nan (Synlett, 2012)
Amines have been used as sacrificial electron donors to reduce photoexcited Ru(II) or Ir(III) complexes, during which they are oxidized to nitrogen radical cations. Recently, the synthetic potential of these nitrogen radical cations have caught synthetic organic chemists’ attention. They have been exploited in various transformations yielding a number of elegant methods for amine synthesis. This article highlights recent developments on nitrogen radical cation chemistry under visible-light photocatalysis.
Keywords: amines; visible light; nitrogen radical cations; ruthenium; iridium